Adjuvant Chemotherapy for T3 Non–Small Cell Lung Cancer with Additional Tumor Nodules in the Same Lobe. Issue 7 (July 2016) - Salazar, Michelle C.; Rosen, Joshua E.; Arnold, Brian N.; Thomas, Daniel C.; Kim, Anthony W.; Detterbeck, Frank C.; Blasberg, Justin D.; Boffa, Daniel J.
ABSTRACT : Introduction: : Adjuvant chemotherapy after surgical resection of non–small cell lung cancer is associated with a survival advantage in several staging scenarios. T3 tumors associated with a separate tumor nodule in the same lobe (formerly "satellite nodules") have a significant risk for systemic failure, yet the efficacy of adjuvant chemotherapy in this setting is unknown. The survival of patients with T3 tumors and additional tumor nodules in the same lobe treated with and without postoperative chemotherapy was evaluated to understand the role of adjuvant chemotherapy in this setting. Methods: : The National Cancer Data Base was queried for patients with T3 tumors with additional tumor nodules in the same lobe between 2010 and 2012. Primary outcomes were 3‐year overall and relative survival (a surrogate of cancer‐specific survival). Results: : A total of 1013 patients with T3 tumors and additional tumor nodules in the same lobe were identified; 56% received multiagent postoperative chemotherapy and 44% were treated with surgical resection only. The use of adjuvant chemotherapy versus resection alone was associated with improved 3‐year overall survival (70% versus 59%, p < 0.001). A Cox model adjusting for patient, tumor, and treatment factors demonstrated that adjuvant chemotherapy was associated with a survival advantage compared with resection alone (hazard ratio = 0.544, p < 0.0001). Relative 3‐year survival was also improved in the adjuvant chemotherapy subgroup (74% versus 64% for the surgery‐only subgroup). Conclusions: : Adjuvant chemotherapy is associated with increased overall survival among patients with T3 tumors with additional pulmonary nodules. Further study is warranted to clarify the role of adjuvant chemotherapy in this setting.